Rpn10-Mediated Degradation of Ubiquitinated Proteins Is Essential for Mouse Development - Hamazaki, Jun (American Society for Microbiology (ASM), 2007)
Rpn10 is a subunit of the 26S proteasome that recognizes polyubiquitinated proteins. The importance of Rpn10 in ubiquitin-mediated proteolysis is debatable, since a deficiency of Rpn10 causes different phenotypes in different organisms. To date, the role of mammalian Rpn10 has not been examined genetically. Moreover, vertebrates have five splice variants of Rpn10 whose expressions are developmentally regulated, but their biological significance is not understood. To address these issues, we generated three kinds of Rpn10 mutant mice. Rpn10 knockout resulted in early-embryonic lethality, demonstrating the essential role of Rpn10 in mouse development. Rpn10a knock-in mice, which exclusively expressed the constitutive type of Rpn10 and did not express vertebrate-specific variants, grew normally, indicating that Rpn10 diversity is not essential for conventional development. Mice expressing the N-terminal portion of Rpn10, which contained a von Willebrand factor A (VWA) domain but lacked ubiquitin-interacting motifs (Rpn10ΔUIM), also exhibited embryonic lethality, suggesting the important contribution of UIM domains to viability, but survived longer than Rpn10-null mice, consistent with a “facilitator” function of the VWA domain. Biochemical analysis of the Rpn10ΔUIM liver showed specific impairment of degradation of ubiquitinated proteins. Our results demonstrate that Rpn10-mediated degradation of ubiquitinated proteins, catalyzed by UIMs, is indispensable for mammalian life.